Novel Core-shell Bioceramic Silica-Berberis vulgaris: Synthesis and Characterization : synthesis of Bioceramic Silica-Berberis core-shell - Chawshli, Mahmood F.; Hamad, Shakhawan K. (Cellular and Molecular Biology, 2023)
Enhancements in bioceramic mixtures represent a significant avenue for achieving superior mechanical and biological properties. Therefore, the present study aimed to extract active compounds from Berberis vulgaris stems and fruits collected from the Khorasan province, employing advanced analytical techniques such as GC-MS and FTIR to elucidate the composition of these extracts. The derived extracts were utilized to synthesize novel nanocomposites, denoted as SiO2-MPS-stem extract and SiO2-MPS-fruit extract. Comprehensive Characterization of these composites was conducted through SEM, EDX mapping, FTIR, and XRD analyses. The characterization measurements validated the successful coating of silica with the extracts, resulting in a core-shell nanostructure with particle sizes below 60 nm. These composites were incorporated into bioceramics for dental root fillings with an equal weight ratio. The bioceramic material was subjected to the same aforementioned characterization techniques, revealing that their sizes fell within the nanoscale range, not exceeding 70 nanometers. The results indicated a core-shell configuration for the nanomaterials, with the shell comprising the bioceramic component of bioceramic-SiO2-MPS-fruit extract and bioceramic-SiO2-MPS-stem extract.